2004
DOI: 10.1038/sj.bjc.6601923
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of epidermal growth factor receptor expression as a predictive factor for response to gefitinib (‘Iressa’, ZD1839) in non-small-cell lung cancer

Abstract: Gefitinib ('Iressa', ZD1839) is an orally active epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor that has demonstrated antitumour activity and favourable tolerability in Phase II studies. We investigated whether EGFR expression levels could predict for response to gefitinib in patients with advanced non-small-cell lung cancer (NSCLC), who received gefitinib (250 mg day À1 ) as part of a worldwide compassionate-use programme. Tissue samples were analysed by immunohistochemistry to assess membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
100
2
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(112 citation statements)
references
References 20 publications
8
100
2
2
Order By: Relevance
“…The gefitinib concentration of 1 M was used as cutoff for sensitivity because this concentration approaches levels observed in serum from patients under treatment with 250 mg/day [6]. In line with other reports [28,33,34] no association between responsiveness to gefitinib and EGFR level was observed.…”
Section: Discussionmentioning
confidence: 59%
“…The gefitinib concentration of 1 M was used as cutoff for sensitivity because this concentration approaches levels observed in serum from patients under treatment with 250 mg/day [6]. In line with other reports [28,33,34] no association between responsiveness to gefitinib and EGFR level was observed.…”
Section: Discussionmentioning
confidence: 59%
“…Indeed, although some authors reported a relationship between EGFR protein expression assessed by IHC and clinical benefit from EGFR tyrosine kinase inhibitors in NSCLC, 13,14 such a correlation was not confirmed by others. 11,36,37 Therefore, the predictive value of EGFR IHC in NSCLC care remains to be validated.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies that evaluated EGFR status by immunohistochemistry did not show any correlation between levels of EGFR protein expression and response to gefitinib or erlotinib. [13][14][15] However, closer analysis of the small subset of responders revealed several themes. Patients who responded to gefitinib tended to be female, Japanese, nonsmokers, and those diagnosed with a particular type of NSCLC termed bronchioalveolar carcinoma (BAC).…”
mentioning
confidence: 99%